THE EFFECT ONLINE LEARNING ON STUDENTS COLLEGE STRESS LEVELS - Wahyunengsih Wahyunengsih; Bella Salsa Risnawati; Eryanti Widya Cahyaningrum (ADIBA : JOURNAL OF EDUCATION, 2022)
Covid 19 is a new and infectious disease caused by SARS COV-2, which is one type of the corona virus. With the new disease, the government is trying to slow its spread by giving an appeal to the public to stay at home and learning is also done online. Online learning makes students need to adapt, and in the adaptation process, stress problems can arise for students. Therefore, we conducted this study with the aim of knowing how much influence online learning has on students' stress levels. This type of study is a quantitative research with an analytical observational method. We collected data for 40 respondents through questions posed online by filling out a questionnaire via the Google Form platform. The data obtained that most of the students experienced stress at a low level (115.5%), some experienced stress at a moderate level (494.9%), some experienced stress at a high level (292.3%), and experienced stress at a very high level. high (110,3%). The results of this study showed that the majority of students' stress levels in online learning were at a moderate level. 3%). The results of this study showed that the majority of students' stress levels in online learning were at a moderate level. 3%). The results of this study showed that the majority of students' stress levels in online learning were at a moderate level.